2021
DOI: 10.1007/s00259-021-05462-5
|View full text |Cite
|
Sign up to set email alerts
|

Can the BMI-based dose regimen be used to reduce injection activity and to obtain a constant image quality in oncological patients by 18F-FDG total-body PET/CT imaging?

Abstract: Purpose PET image quality is influenced by the patient size according to the current guideline. The purpose was to propose an optimized dose regimen to yield a constant image quality independent of patient size to meet the clinical needs.Methods A first patient cohort of 78 consecutives for oncological patients (59.7±13.7 years) who underwent a total-body PET/CT scan were retrospectively enrolled to develop the regimen. The patients were equally distributed in four BMI groups according to WHO criteria. The liv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 18 publications
(30 reference statements)
1
13
0
Order By: Relevance
“…Previous studies show that patients with a larger BMI consistently generate poorer image quality when using OSEM reconstruction [ 17 , 24 ]. Our previous study also showed that the acceptability of the SNR L should be more than 14.0 to meet the needs of image quality [ 25 ]. Consistent with the previous study, the SNR of the obese group could also could meet the need for image quality in the OSEM2 and HYPER Iterative groups with a 15-min duration, whereas OSEM3 showed image with sub-optimal noise.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies show that patients with a larger BMI consistently generate poorer image quality when using OSEM reconstruction [ 17 , 24 ]. Our previous study also showed that the acceptability of the SNR L should be more than 14.0 to meet the needs of image quality [ 25 ]. Consistent with the previous study, the SNR of the obese group could also could meet the need for image quality in the OSEM2 and HYPER Iterative groups with a 15-min duration, whereas OSEM3 showed image with sub-optimal noise.…”
Section: Discussionmentioning
confidence: 99%
“…The newest total-body PET/CT can achieve lower injection dose, faster scanning speed, and higher resolution than the others (15,40,41). Therefore, it is more valuable in clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the total-body PET/CT, uEXPLORER (United Imaging Healthcare, Shanghai, China) with the 194-cmlong Field of View (FOV), has ultrahigh system sensitivity and spatial resolution. Thus, it dramatically improves image quality and ability to detect small lesions and distant metastases (14,15). Regarding semiquantitative parameters, several studies have found that the standard uptake value ratio (SUR) is a better predictive index than tumor maximum standard uptake value (SUVmax) (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…The image quality was scored from 3 perspectives: the overall impression of the image quality, the image noise, and the lesion detectability. Score were based on a 5-point Likert scale, as follows: Score 1, image with non-diagnostic quality, excessive noise, or unfavorable lesion contrast; Score 2, acceptable image but with sub-optimal noise and lesion depiction leading to impaired diagnostic con dence; Score 3, image with quality equivalent to those used in clinical practice; Score 4, image with quality superior to the average image quality; Score 5, image with excellent quality, optimal noise, sharp lesion depiction, and free of artifact, providing diagnosis with full con dence [11]. A score of 3 was deemed as acceptable image quality in routine clinical practice in our center.…”
Section: Qualitative Image Analysismentioning
confidence: 99%
“…Additionally, the injection activity of the tracer, acquisition time, and patient-speci c photon attenuation, particularly for large body masses, can in uence image quality. Regarding constant acceptable image quality, we previously investigated the in uence of patient size on image quality and proposed a dose regimen based on BMI, demonstrating the feasibility of constant image quality for 18 F-FDG total-body PET/CT [11]. In addition, adjusting the duration time per bed position based on scanner sensitivity and patient-speci c attenuation might result in uniform image noise [12].…”
Section: Introductionmentioning
confidence: 99%